2021
DOI: 10.1088/1361-6641/ac3dd3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced switching ratio of sol–gel-processed Y2O3 RRAM device by suppressing oxygen vacancy formation at high annealing temperatures

Abstract: Sol–gel-processed Y2O3 films were used as an active-channel layer for RRAM devices. The effect of post-annealing temperature on structural, chemical, and electrical characteristics was investigated. The Y2O3-RRAM devices, comprising electrochemically active metal electrodes, Ag, and Indium tin oxide (ITO) electrodes exhibited the conventional bipolar RRAM device operation. The fabricated Ag/Y2O3/ITO RRAM devices, comprising 500-℃ annealed Y2O3 films, exhibited less oxygen vacancy and defect, which reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Several Y 2 O 3 -based RRAM devices have shown that the resistive switching memory behavior can be attributed to the formation and destruction of an O v –based conductive path. ITO/Y 2 O 3 /Au RRAM devices do not show these characteristics of RRAM devices [ 14 ], indicating that the formation and rupture of the metallic conductive path, originating from the oxidation and reduction processes from Ag electrodes, are the main mechanisms of ITO/Y 2 O 3 /Ag RRAM devices. The fabricated devices showed a high-resistance state (HRS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Y 2 O 3 -based RRAM devices have shown that the resistive switching memory behavior can be attributed to the formation and destruction of an O v –based conductive path. ITO/Y 2 O 3 /Au RRAM devices do not show these characteristics of RRAM devices [ 14 ], indicating that the formation and rupture of the metallic conductive path, originating from the oxidation and reduction processes from Ag electrodes, are the main mechanisms of ITO/Y 2 O 3 /Ag RRAM devices. The fabricated devices showed a high-resistance state (HRS).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Y 2 O 3 has emerged as a promising active material for preparing RRAM devices [ 10 , 11 , 12 ]. Forming-free RRAM devices can be prepared using oxygen vacancy (O v )–rich Y 2 O 3 [ 13 , 14 ]. The forming process requires an additional large voltage for the initial conductive filament (CF), occasionally resulting in electrode destruction.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, the deposited top Ag electrode served as the main source for the formation of a conductive path between the top and bottom ITO electrodes. Our previous study demonstrated that using inert top Au electrodes, the fabricated device showed no resistive switching memory properties, indicating that the fabricated RRAM device was a type of ECM RRAM [ 11 ]. The initial resistance status was a high-resistance status (HRS).…”
Section: Resultsmentioning
confidence: 99%
“…For this imitation, memory devices with high density, high performance, and low-power operation are required. Several metal–oxide active channel materials, such as SiO x , ZrO 2 , TiO x , Hf x O, and Y 2 O 3 , have been considered for RRAM device fabrication [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Y 2 O 3 is characterized by a high dielectric constant, large optical bandgap, and fast internal ion transport and is therefore considered quite attractive for use in such devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to realize a neuromorphic computing system that mimics the human brain, RRAMs have been used because of the aforementioned advantages. Many metal oxides such as SiO x , ZrO 2 , TiO x , Hf x O, and Y 2 O 3 have been studied for use in RRAM devices [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among these, Y 2 O 3 demonstrates advantages over other metal oxides.…”
Section: Introductionmentioning
confidence: 99%